High-Intensity Interval Training in Metabolic Diseases: Physiological Adaptations. (September 2021) - Batrakoulis, Alexios; Jamurtas, Athanasios Z.; Fatouros, Ioannis G.
Abstract : Supplemental digital content is available in the text. Apply It!: From this article, the reader should understand the following concepts: The impact of high-intensity interval training on physiological and psychological responses among individuals with metabolic diseases. A strategy for prescribing high-intensity interval training protocols in adults with obesity, type 2 diabetes, dyslipidemia, and metabolic syndrome.